Solubility of sorbic acid in organic mono-solvents: calculation of Abraham model solute descriptors from measured solubility data. (3rd September 2017) - Barrera, Maribel; Hart, Erin; Horton, Melissa Y.; Higgins, Elizabeth; Cheeran, Sarah; Little, Grace E.; Singleton, Hunter; Calhoon, Donavyn; Gillispie, Kyle; Khalil, Febronia; Williams, Randall; Acree, William E.; et al.
ABSTRACT: Experimental mole fraction solubilities are reported for sorbic acid dissolved in methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, 1-hexanol, 2-propanol, 2-methyl-2-propanol, 2-pentanol, diisopropyl ether, methyl tert -butyl ether, tetrahydrofuran and 1, 4-dioxane at 298.15 K. Results of the experimental measurements, combined with a published water-to-octanol partition coefficient and published solubility data for sorbic dissolved in acetone, ethyl acetate and acetonitrile, were used to calculate Abraham model solute descriptors for the sorbic acid monomer. The calculated solute descriptors were found to describe the measured solubility and partition coefficient data to within 0.10 log units. The calculated solute descriptors can be used to predict sorbic acid solubilities at 298.15 K in additional organic solvents in which sorbic acid is expected to exist predominately in monomeric form.